Wine tourism in the Auckland region : an analysis of the relationship between the wine and tourism industries as well as the significance of wine tourism as a tourist attraction : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Management at Massey University - Winter, William Nash (Massey University, 2003)
Originally designed for a conservative domestic market, devoid of wine drinking traditions, wine production in New Zealand, by taking advantage of the recent trend in the liberalisation of legislation, has now expanded to the extent that other markets including wine tourism are becoming increasingly crucial if further enlargement of the industry is to continue. Within New Zealand, as with many countries, tourism both international and domestic, has become a major contributor towards economic prosperity. Overtaking the more conventional hedonistic tourism pursuits of past years, special interest or activity based tourism is now gaining momentum both within New Zealand and overseas. The availability of suitable attractions and activities are vital if this burgeoning industry is to further expand in the future. Particularly this is so in the Auckland region which is struggling to maintain and increase visitation levels by both overseas and domestic tourists. Wine tourism entails more than just visiting wineries and vineyards. Rather it is the summation of a number of unique experiences – the "winescape". This includes ambience, landscape, surrounding social environment, regional culture, cuisine, local wine styles, and a variety of unique leisure activities that makes wine tourism popular with a growing number of travellers. Wine tourism can be considered as a form of consumer behaviour, based not only on the appeal of wine and wine regions but also involving development, marketing and promotional strategies for both the wine industry and market-place destination in which wineries and wine-related experiences are the predominant attractions. Internationally wine tourism is expanding rapidly throughout most wine producing regions in the world, although New Zealand including Auckland, is further behind in both recognition and extent than other comparable New World countries. In the case of Auckland, the growth and nature of wine tourism varies considerably as between the five sub-regions constituting the Auckland Wine Region. To further investigate wine tourism generally and more specifically in the Auckland Wine Region, a wine tourism market model has been constructed in order to consider the demand, supply and destinational aspects of the wine tourism market-place. Within the context of the Auckland Wine Region, the research was designed by using the model, to explain the various components of wine tourism and their interrelationships. At a more general level it also seeks to consider the positioning of wine tourism within the ambit of the tourism attractions of the greater Auckland area.
Keywords: Tourism; Wine industry; New Zealand